Influence of Company Size on Accounting Information for Decision-Making of Management - Horvat, Tatjana; Mojzer, Jožica (Naše gospodarstvo/Our economy, 2019)
The aim of this paper is to show the importance of accounting information for management, especially in medium-sized companies. Sampling was carried out according to the accidental principle, after which we selected 300 medium-sized and large companies. We used the questionnaire, which was standardized and implemented online. Two hypothesis were tested with a chi-square test and contingency table. In this study of Slovenian large and medium companies, we want to find out whether the size of the company has an impact on organizing a specific controlling service in a company and whether, in large companies, heads of accounting are more often members of management than in medium- sized enterprises. We discovered a bias between organizing a specific controlling department and the size of a company, and that large companies have more often organized a special controlling service than medium-sized enterprises. We also discovered the accounting officer’s membership in a company’s management team is not related to the size of a company. The results of the research could be used in controlling in medium-sized companies, where we suggest that management accounting in these companies is part of management decisions.